A Tablet Matrix with Hibiscus rosa Sinensis Leave Mucilage for Effective Treatment of Rare Lymphangioleiomyomatosis Using Sirolimus - Hindustan Abdul Ahad; Haranath Chinthaginjala; Yarragunta Roja; Kandlapalli Swathi; Pandre Shravya; Anam Rashi (Shiraz University of Medical Sciences, 2022)
Using a blend of herbal and synthetic polymers, the authors aim to extend the release of Sirolimus from the tablets. Sirolimus was used as a model drug, Hydroxy Propyl Methyl Cellulose was used as a synthetic polymer, and mucilage from Hibiscus rosa sinensis leaves was used as a natural polymer in this study. In addition to treating Lymphangioleiomyomatosis damage and suppressing body rejection toward transplanted organs, sirolimus is also an orphan drug. The Sirolimus matrix tablets are made with a combination of H. rosa sinensis leaf mucilage and Hydroxypropyl Methyl Cellulose. We assessed the flow properties of the blend and classified the designed tablets for official and non-official tests, including Sirolimus discharge. Sirolimus matrix tablets have passable pre- and post-formulation parameters with good Sirolimus content. A chemical interaction between Sirolimus and the polymers used in the study was not observed. Researchers also discovered that H. rosa sinensis leaf mucilage can be a good polymer in combination with other polymers for prolonged drug release. Please cite this article as: Hindustan Abdul Ahad*1, Chinthaginjala Haranath1, Yarragunta Roja, Kandlapalli Swathi, Pandre shravya, Anam Rashi. A Tablet Matrix with Hibiscus Rosa Sinensis Leave Mucilage for Effective Treatment of Rare Lymphangioleiomyomatosis Using Sirolimus. Trends in Pharmaceutical Sciences. 2022;8(1):43-50.doi: 10.30476/TIPS.2021.90567.1087